Protein interactions during flour mixing using wheat flour with altered starch. (15th September 2017) - Wang, Xiaolong; Appels, Rudi; Zhang, Xiaoke; Diepeveen, Dean; Torok, Kitti; Tomoskozi, Sandor; Bekes, Ferenc; Ma, Wujun; Sharp, Peter; Islam, Shahidul
Highlights: Extended knowledge of dough proteins responses to mixing and thermal treatment. Variations in protein interactions have been identified with altered starch in dough. Dough rheological performances are associated with starch protein interface. Findings provide new entry points for modifying final product attributes. Proteins associated with starch interactions are distributed over 7 chromosome groups. Abstract: Wheat grain proteins responses to mixing and thermal treatment were investigated using Mixolab-dough analysis systems with flour from two cultivars, Ventura-26 (normal amylose content) and Ventura-19 (reduced amylose content). Size exclusion high performance liquid chromatography (SE-HPLC) and two-dimensional gel electrophoresis (2-DGE) analysis revealed that, stress associated and metabolic proteins largely interacted with dough matrix of Ventura-26 after 26 min (56 °C); gliadins, avenin-like b proteins, LMW-GSs, and partial globulins showed stronger interactions within the dough matrix of Ventura-26 at 32 min/C3 (80 °C), thereafter, however, stronger protein interactions were observed within the dough matrix of Ventura-19 at 38 min/C4 (85 °C) and 43 min (80 °C). Thirty-seven proteins associated with changes in dough matrix due to reduced amylose content were identified by mass spectrometry and mainly annotated to the chromosome group 1, 4, and 6. The findings provide new entry points for modifying final product attributes.